Tempo histórico, masculinidades e transgressão na obra Fight Club (1996) - Santos , Dyener (2021)
The present research proposes to analyze and debate the literary work Fight Club (1996), by the North American writer Chuck Palahniuk, based on historical analysis. Considered as a classic, well-referenced by David Fincher’s film, it carries elements that ironically and critically represent man in the American society of the 90s. One of the characters evidenced as a model of manhood is Tyler Durden, who is the alter ego of the protagonist and narrator, and responsible for many events of the plot. When Tyler says that “it’s only after we’ve lost everything that we will be free to do anything”, it is possible to see the proximity of teleological meaning as in Christianity, as a philosophical theology of history. The character of Tyler is often portrayed not only as a role model man but as an entity that projects his expectations in search of a purpose to chaos, eschatologically. What the space monkeys and Tyler experience, as individuals who shared the same space of experience, thus evidenced the breaking or overcoming of a form of manhood forged by consumerism and modernity. Casting expectations regarding an undefined perfect place. The objective of the present research consists of identifying whether the manhood models present in Fight Club, as a dystopian work of literature, make it possible to understand the concept of historical time present in the literary narrative. Is the model of social transformation denoted in the novel, one of rescuing the past or forgetting that historical time? Or even the construction of a future to be dazzled?